Hydrographic changes in the Agulhas Recirculation Region during the late Quaternary - D. K. Naik; R. Saraswat; N. Khare; A. C. Pandey; R. Nigam (Climate of the Past, 2014)
The strength of Southern Hemisphere westerlies, as well as the positions of the subtropical front (STF), Agulhas Current (AC) and Agulhas Return Current (ARC) control the hydrography of the southwestern Indian Ocean. Although equatorward migration of the STF and reduction in Agulhas leakage were reported during the last glacial period, the fate of ARC during the last glacial–interglacial cycle is not clear. Therefore, in order to understand changes in the position and strength of ARC during the last glacial–interglacial cycle, here we reconstruct hydrographic changes in the southwestern Indian Ocean from temporal variation in planktic foraminiferal abundance, stable isotopic ratio (δ 18 O) and trace elemental ratio (Mg/Ca) of planktic foraminifera Globigerina bulloides in a core collected from the Agulhas Recirculation Region (ARR) in the southwestern Indian Ocean. Increased abundance of G. bulloides suggests that the productivity in the southwestern Indian Ocean increased during the last glacial period which confirms previous reports of high glacial productivity in the Southern Ocean. The increased productivity was likely driven by the intensified Southern Hemisphere westerlies supported by an equatorward migration of the subtropical front. Increase in relative abundance of Neogloboquadrina incompta suggests seasonally strong thermocline and enhanced advection of southern source water in the southwestern Indian Ocean as a result of strengthened ARC, right through MIS 4 to MIS 2, during the last glacial period. Therefore, it is inferred that over the last glacial–interglacial cycle, the hydrography of the southwestern Indian Ocean was driven by strengthened westerlies, ARC as well as a migrating subtropical front.